ANALISIS AWAL KERAGAMAN MOLEKULAR KELAPA SAWIT (Elaies guineensis Jacq.) MENGGUNAKAN LIMA PRIMER SSR (Simple Sequences Repeats) - Arnen Pasaribu (Talenta Publisher, 2017)
Molecular variance is very important. The information resulted from the analysis at the molecularlevel can advantage as a first step to manage breeding programs. The aim of thisresearch was to determine a molecular variance in palm oil-based on SSR primer usingFR0465, FR391, FR304, FR0350 and FR3693 primers. The research was conducted atTerpadu Laboratory, Faculty of Medicines, North Sumatera University from September 2015to February 2016. Gen Alex ver. 6.501, Power Marker 3.25 and software DARwin SoftwareVersion 6 was used to calculate and analysis. The result of this research showed that the value ofmolecular variants of Palm Oil (E. guineensis) was 62.43%, polymorphic information content(PIC) was 0.338. The measure of fragment about 120 bp – 496 bp. FR02350 has the highest numberof alel and the value of expected heterozygote (He) was 0.685.